2015
DOI: 10.1016/j.virol.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Several residues within the N-terminal arm of vesicular stomatitis virus nucleoprotein play a critical role in protecting viral RNA from nuclease digestion

Abstract: The nucleoprotein (N) of vesicular stomatitis virus (VSV) plays a central role in transcription and replication by encapsidating genome RNA to form a nucleocapsid as the template for the RNA synthesis. Using minigenome system we evaluated the roles of 21 amino acids of the N-terminal arm of N in forming functional N-RNA templates and found that three triple-amino-acid substitutions (TVK4-6A3, RII7-9A3, and VIV13-15A3) and one single-amino-acid substitution (R7A) resulted in RNA synthesis loss. But all the muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The SFV replicon and helper plasmids were kindly donated by Dr. Markus U. Ehrengruber, Department of Biology, Kantonsschule Hohe Promenade, Zurich, Switzerland. The mutated vesicular stomatitis virus rVSV-EGFP-NR7A were prepared as described previously 33,34 .…”
Section: Methodsmentioning
confidence: 99%
“…The SFV replicon and helper plasmids were kindly donated by Dr. Markus U. Ehrengruber, Department of Biology, Kantonsschule Hohe Promenade, Zurich, Switzerland. The mutated vesicular stomatitis virus rVSV-EGFP-NR7A were prepared as described previously 33,34 .…”
Section: Methodsmentioning
confidence: 99%
“…Using a well‐established VSV minireplicon assay, we found that three triple‐amino acid substitutions (TVK4‐6A3, RII7‐9A3, and VIV13‐15A3) and one single‐amino acid substitution (R7A) within the N‐terminal 21 amino acids of the NC resulted in RNA synthesis loss, whereas all the mutants maintained the ability to oligomerize and encapsidate viral RNA. Furthermore, Northern blotting analysis of nuclease sensitivity of gRNAs encapsidated by the NC or mutants showed that all the mutants failed to protect viral RNAs from nuclease digestion, suggesting that NCs are also involved in the protection of viral gRNA from nuclease digestion for the formation of a functional viral RNA template . Similarly, a recent study showed that the positively charged and polar amino acids in the surface cleft of the NC of tomato spotted wilt virus are critical for viral RNA template function, and a subsequent study found that the NC of tomato spotted wilt virus was indeed able to protect the RNA from the degradation of RNase; the mutants of NC, R94A/R95A and K183A/Y184A, which lost the RNA‐binding activity, were no longer able to protect the RNA from RNase degradation …”
Section: The Function Of Nc In Virus Life Cyclementioning
confidence: 97%
“…But these VSVs have high cytotoxicity that can lead to rapid death of mice, which limits long-term structural observation and gene manipulation or function research, restricting their applications in neuroscience [23]. Several mutants have been obtained by mutating the N gene related to the replication of VSV [24][25][26][27]. After mutating the seventh amino acid of the N protein (VSV-N R7A ), the replication speed of the virus decreased by 2-3 orders of magnitude within 24 h [24,25], which might be used as a better tracer, but whether it still has the ability of anterograde trans-synaptic labeling is still unknown.…”
Section: Introductionmentioning
confidence: 99%